APPLICATION OF BACK KICK TECHNOLOGY AND ACTION ANALYSIS OF BEIJING YOUNG MEN'S TAEKWONDO ATHLETES - Xinyu, Guo; Hongwei, Yan (ASEAN Journal of Sport for Development and Peace, 2022)
The latest competition rules of taekwondo expand the score of turning technique and encourage athletes to use difficult techniques to increase the diversity of techniques and the appreciation of competitions. This paper obtains the characteristics of important action links of scoring technology from two aspects of technical and tactical application and technical action analysis. Back kick scoring technology mostly appears in the tactical state, is an important means of scoring. From the point of view of time characteristics, the speed of the back kick technique in the turning stage becomes the key to successful application, and there are major defensive hidden dangers in the kick reduction stage. The hip joint angle on one side of kicking leg of the kick scoring technique is less than that of the non- scoring technique in the knee lifting stage and the knee joint angle in the turning stage, and the knee joint angle of the non- scoring technique is less than that of the scoring technique in the knee lifting stage and kicking stage. Insufficient extension is an important factor that cannot score.